2022
DOI: 10.1002/ar.25011
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in imaging, anatomy, and mechanics of crocodylian jaw muscles

Abstract: New imaging and biomechanical approaches have heralded a renaissance in our understanding of crocodylian anatomy. Here, we review a series of approaches in the preparation, imaging, and functional analysis of the jaw muscles of crocodylians. Iodine‐contrast microCT approaches are enabling new insights into the anatomy of muscles, nerves, and other soft tissues of embryonic as well as adult specimens of alligators. These imaging data and other muscle modeling methods offer increased accuracy of muscle sizes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Holliday et al [ 48 ] compared the volumes obtained from the frustum approach, the Avizo approach, and segmented muscles, and found that the Avizo approach produced similar volumes to the segmentation (more similar than the frustum approach) except for the mPTd. As noted by Holliday et al [ 48 ], the mPTv and mPTd are more prone to subjectivity since they are less constrained by the surrounding bones than the other muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holliday et al [ 48 ] compared the volumes obtained from the frustum approach, the Avizo approach, and segmented muscles, and found that the Avizo approach produced similar volumes to the segmentation (more similar than the frustum approach) except for the mPTd. As noted by Holliday et al [ 48 ], the mPTv and mPTd are more prone to subjectivity since they are less constrained by the surrounding bones than the other muscles.…”
Section: Discussionmentioning
confidence: 99%
“…9: 220519 but using manual measurements; thereby both approaches will underestimate the length of curved muscles compared to our Blender approach (in an earlier iteration of the Avizo approach, Lautenschlager [28] used the Avizo statistics module to calculate muscle cross section, but that approach assumes that all muscles are aligned with the scan axes, which is often not the case). Holliday et al [48] compared the volumes obtained from the frustum approach, the Avizo approach, and segmented muscles, and found that the Avizo approach produced similar volumes to the segmentation (more similar than the frustum approach) except for the mPTd. As noted by Holliday et al [48], the mPTv and mPTd are more prone to subjectivity since they are less constrained by the surrounding bones than the other muscles.…”
Section: Muscle Reconstruction Toolmentioning
confidence: 99%
“…The authors also found that air flow within the pterygoid bullae may be responsible for the popping sound male gharials create. Lessner and Holliday (2022) used contrast‐enhanced microCT to model the brain and cranial nerves in an ontogenetic series of alligators. They found cranial nerves to be largely consistent in their paths and pattern indicating that they are highly conserved neurological tissues as expected and identified key stages in ganglion formation and brain shape changes.…”
Section: Figurementioning
confidence: 99%
“…Contrast-enhanced imaging is proving to be revolutionary for studying vertebrate morphology. Highlighting imaging approaches to soft tissue morphology, Holliday et al (2022) review new approaches in contrast imaging of crocodylians. In addition to comparing approaches in imaging large and small specimens of extant species, they present a series of examples of imaging and modeling jaw muscle anatomy and 3D muscle architecture.…”
mentioning
confidence: 99%
“…He has become one of the leading comparative reptilian anatomists/paleo‐anatomists in the world today and has published extensively. Casey's science has often graced our pages covering, for example: new cephalic vascular anatomy in flamingos (Holliday, Ridgely, Balanoff, & Witmer, 2006); new insights into dinosaur jaw anatomy (Holliday, 2009); study of trigeminal nerve morphology in alligators with implications for understanding crocodyliform facial sensation and evolution (George & Holliday, 2013); studies on the frontoparietal fossa and dorsotemporal fenestra of archosaurs for interpreting anatomy in dinosaurs (Holliday, Porter, Vliet, & Witmer, 2020); explorations of the nose of gharials to understand airflow and acoustics (Bourke, Fontenot, & Holliday, 2022, this volume); new approaches in imaging to understand anatomy and mechanics of crocodilian jaw muscles (Holliday et al, 2022, this volume); biomechanical assessment of the craniomandibular complex of the notosuchian, Araripesuchus gomesii (Nieto, Degrange, Sellers, Diogo, & Holliday, 2022, this volume); and the effects of skull flattening on suchian jaw muscle evolution (Sellers et al, 2022, this volume). Thanks to both Casey and Emma (Figure 1a, b) for sharing their best science so often in our journal!…”
Section: Figurementioning
confidence: 99%